Hybrid methods of space radiation shielding for astronauts against deep-space radiation - Pal Chowdhury, Rajarshi (Kansas State University, 2020)
Protecting astronauts against the harsh radiation environment of space is one of the major hurdles to human presence in space in the twenty-first century. Future exploration class missions to the Moon and Mars will require a long-duration presence of astronauts in space outside of the protective barrier of the Earth's atmosphere and geomagnetic field. Space radiation outside of the protection of Earth is a complex hybrid environment of highly energetic and heavy charged cosmic ions and energetic protons generated as a result of solar activity. It was established in previous studies that conventional radiation shielding methods that use materials to slow down and fragment the heavy charged ions are incapable of protecting per NASA's career space radiation limit, for deep-space, long-term missions. Therefore, other strategies must be used to shield astronauts on long-duration space missions adequately. Electrostatic radiation shielding, in which an electrostatic field is used to deflect charged particles, was investigated as an alternative by various researchers. All prior investigations concluded that the magnitude of potentials needed to generate a field that can provide significant protection is beyond the reach of present-day technology. In this work, a set of configurations for electrostatic radiation shielding was investigated. This work proposes a novel concept of using multiple conductors of lower-magnitude electric field and repetitively arranging them in three-dimensional space to generate a cumulative electric field, which, together with passive shielding, can provide significant protection. Multiple combinations of such configurations were identified. A set of optimized electrostatic settings and passive shielding materials were used to characterize shielding efficacy against deep-space radiation.
Keywords: Active Shielding; Passive Shielding; Space Radiation; Risk Assessment; Space Radiation Dosimetry; Hybrid Shielding